King Arthur in fact and legend - Ashe, Geoffrey (Camden [N.J.] : T. Nelson, 1971)
Traces the development of the Arthurian legend comparing it with the facts of King Arthur's life as they have been reconstructed from historical records and archaeological finds
Bibliography: p. [153]
Keywords: Arthur, -- King; Arthurian romances -- Sources; Britons -- Kings and rulers -- Folklore; Great Britain -- History -- To 1066.; Great Britain -- Antiquities, Celtic